Introduction - Sakal, Halil Burak; Yildiz, Merve (Cappadocia Journal of Area Studies, 2024)
The December 2024 issue of our journal brings together our esteemed readers with eight different articles. In this issue, there are three research articles, two opinion articles and three publication reviews. The first research article, written by Hasan Ali Karasar, deals with Sinason, an Ottoman village in 18th century Central Anatolia. It reveals the unique administrative, socio-economic and legal dynamics of the village through ten archival documents dating between 1696 and 1782. It sheds light on Sinason's economic contributions, agricultural production and its importance in the Ottoman financial system through its support for the financing of imperial projects. Nayan Mitra is the author of the research article on corporate social responsibility culture in India and Turkiye. The article, which contributes significantly to the research on corporate social responsibility and sustainability, analyses the corporate social responsibility practices of companies in India and Turkiye and compares their similarities and differences. The third research article, authored by Aygül Akkuş, presents the role of development agencies in regional development and discusses the role of central government on development agencies. The opportunities and limitations of development agencies, which are positioned as an interface between central and local governments, are evaluated together. The first review essay is by Ali Caner İncesu, who analyses Turkiye-Paraguay diplomacy through trade relations. This fourth study analyses developments since the implementation of Turkiye's Latin American Action Plan, which was announced in 2006. Providing a comprehensive review of the historical, economic and political contexts, supported by data and relevant examples, the assessment addresses a relatively under-researched topic, filling a gap in the literature on Turkiye's relations with Latin America. Another important contribution is that it provides actionable insights for policymakers and the business community. Ali Kiriktas is the author of the fifth paper, which is another review essay. In this essay, which deals with the understanding of individual and society in Chinese civilisation through the works of Lu Xun, one of the important writers of modern Chinese literature, the difficulties experienced in the transition from tradition to modernism are included. The first book review in the publication evaluation section belongs to Tuğrul Keskin. Keskin made a comprehensive review of Can Ulusoy's book ‘Chinese Political Elites in the Context of Chinese Political Thought and Political History Volume 1 (1840 - 1978)’ published by Cappadocia University Press in 2023. The second book review is the review of the editorial book titled ‘Ukraine’ published by Valery Morkva and published by Atatürk Research Centre in 2024. Finally, Ayşe Melek Özgümüş reviews Katja Hoyer's ‘Blood and Iron: The Rise and Fall of the German Empire (1871-1918)’ published by Vakıfbank Kültür Yayınları in 2024. We would like to thank all the authors who have contributed to this issue of our journal by submitting their works and all the referees who have laboured in the evaluation process of these works; we hope that the ongoing interest in our journal from the national and international academic community will continue.